Siloxane polymers, siloxane polymer compositions and shaped bodies
Patent Information
- Application Number
- CN202180060131.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-06
- Filing Date
- 2021-07-29
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2041-07-29
AI Technical Summary
[0068]通过本发明,可提供在主链含有倍半硅氧烷单元和链状硅氧烷单元、在侧链具有笼型倍半硅氧烷结构的硅氧烷聚合物和所述硅氧烷聚合物的制造方法。另外,通过在基材涂布将所述硅氧烷聚合物溶解于有机溶媒中而成的组合物,在进行煅烧后从基材剥离,可获得利用了侧链的笼型倍半硅氧烷的凝聚力(物理交联)的高透明、可挠性的热线膨胀系数低的膜。
Smart Images

Figure CN116209704B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a novel siloxane polymer in which a cage-like silsesquioxane is introduced into the side chains of a siloxane polymer comprising a double-decker silsesquioxane (one of the cage-like silsesquioxanes) and a chain siloxane, a siloxane polymer composition containing the same, and a molded article thereof. Furthermore, it relates to a siloxane polymer compound as an intermediate for manufacturing the siloxane polymer. Background Technology
[0002] Cage-type or bilayer-type silsesquioxanes, obtained by hydrolysis and condensation of trialkoxysilanes or trichlorosilanes, possess a rigid inorganic framework similar to the basic building blocks of silicon dioxide containing Si-O bonds, and have a structure formed by organic groups bonded to each silicon atom. Furthermore, the organic groups (reactive or non-reactive groups) bonded to silicon atoms can be selected based on purposes such as improving affinity for various polymer materials or resin modification caused by reactions, thus making them suitable research objects in the field of organic-inorganic hybrids.
[0003] Polymers containing cage-like silsesquioxane backbones in their main chain can significantly improve properties such as heat resistance, transparency, and hydrophobicity that cannot be achieved using only organic polymers. Polyimide-based polymers (see Non-Patent Literature 1 and 2), polyazoalkane-based polymers (see Non-Patent Literature 3), and polysiloxane-based polymers (see Non-Patent Literature 4) are known examples.
[0004] Among polymers whose main chain contains a bilayer silsesquioxane backbone, which is one of the cage-like silsesquioxanes, various types are known, including polyimide-based (see Non-Patent Documents 5 and 6), polysiloxane-based (see Patent Documents 1-5, Non-Patent Documents 7-10), polybenzoxazine-based (see Non-Patent Document 11), and polyurethane-based (see Non-Patent Document 12) (see Non-Patent Documents 13 and 14). In particular, in the polysiloxane-based polymers, by introducing crosslinking functional groups into the molecular structure and chemically crosslinking using a crosslinking agent, molded articles with excellent transparency and heat resistance have been developed (see Patent Documents 3-5).
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 2010-120901
[0008] Patent Document 2: Japanese Patent Application Publication No. 2006-22207
[0009] Patent Document 3: Japanese Patent Application Publication No. 2008-280420
[0010] Patent Document 4: Japanese Patent Application Publication No. 2010-116464
[0011] Patent Document 5: Japanese Patent Application Publication No. 2010-116462
[0012] Non-patent literature
[0013] Non-patent literature 1: Chemistry Letters, 2014, 43, 1532-1534
[0014] Non-patent literature 2: RSC Advances, 2016, 6, 31751-31757
[0015] Non-patent literature 3: ACS Macro Letters, 2018, 7, 641-645
[0016] Non-patent literature 4: *Polymer Chemistry*, 2015, 6, 7500-7504
[0017] Non-patent literature 5: *Macromolecules*, 2007, 40, 5698-5705
[0018] Non-Patent Literature 6: Macromolecules, 2008, 41, 3481-3487
[0019] Non-patent literature 7: Macromolecules, 2009, 42, 3309-3315
[0020] Non-patent literature 8: Chemistry Letters, 2012, 41, 622-624
[0021] Non-Patent Literature 9: Polymer, 2017, 127, 8-14
[0022] Non-patent literature 10: *Polymer*, 2016, 86, 113-119
[0023] Non-patent literature 11: Macromolecules, 2018, 51, 9602-9612
[0024] Non-Patent Literature 12: *Polymer Chemistry*, 2013, 4, 1491-1501
[0025] Non-patent literature 13: *Current Organic Chemistry*, 2017, 21, 2794-2813
[0026] Non-patent literature 14: Polymers, 2019, 11, 2098 Summary of the Invention
[0027] The problem that the invention aims to solve
[0028] Flexible electronic components using heat-resistant transparent plastic films on substrates not only offer increased freedom in shape, expanding the design scope, but also provide heat resistance during component manufacturing. This drives their adoption in next-generation components requiring thinness and lightweight designs, such as smartphones, tablets, and organic electroluminescent (EL) displays. Extensive development is underway not only of transparent polyimides, polyamides, and polyetheretherketones, but also of polymers with cage-like silsesquioxane backbones in their main chains. However, many challenges remain in improving transparency, heat resistance, coefficient of linear expansion, and smoothness.
[0029] For example, non-patent literature 1-2 reports the successful synthesis of polyimides with a main chain containing a cage-like silsesquioxane backbone, exhibiting excellent heat resistance (T). d5 =483℃), low linear expansion (81.3ppm / K, room temperature ~ 350℃), but transmittance at 360nm is limited to 80%, and a slight yellow tint is observed. Non-patent literature 6 reports the successful synthesis of a polyimide with a bilayer silsesquioxane backbone as one of the cage-like silsesquioxanes in the main chain, which also has excellent heat resistance (T = 483℃), low linear expansion (81.3ppm / K, room temperature ~ 350℃), but transmittance at 360nm is limited to 80%, and a slight yellow tint is observed. d5 =500℃), low dielectric constant (1MHz: 2.63, 100KHz: 2.65) or low water absorption (40~80℃: <1%), but a yellow coloring suggesting the presence of charge-transfer complexes was observed. Patent documents 3-5 successfully synthesized siloxane polymers with a bilayer silsesquioxane backbone in the main chain. By introducing crosslinking functional groups into the molecular structure and using intermolecular chemical crosslinking or crosslinking agents, colorless, transparent polymers with heat resistance (T) were developed. d5 It can form a good molded body (467~540℃), but in addition to the time required for intermolecular chemical cross-linking or reaction with cross-linking agents, there are still many technical challenges in terms of high transparency (haze: <1%, total light transmittance: >90%) required for flexible electronic components and low linear expansion (<200ppm).
[0030] Technical means to solve the problem
[0031] In order to develop a siloxane polymer that does not require chemical crosslinking and contains a bilayered silsesquioxane backbone with high transparency and low linear expansion in the main chain, the inventors have repeatedly studied various methods. They discovered that introducing a cage-like silsesquioxane backbone into the side chains of this siloxane polymer can suppress molecular mobility and strengthen intermolecular cohesion. In other words, the aforementioned problem can be solved by this invention.
[0032] The embodiments of the present invention include the following structures.
[0033] [1] A siloxane polymer having repeating units represented by formula (1) and formula (4), with end groups represented by formula (5L) and formula (5R) at the left and right ends;
[0034]
[0035] Equation (5L) represents the terminal base of the left-hand bond with the equation, and (5R) represents the terminal base of the right-hand bond with the equation;
[0036] A represents the following structure;
[0037]
[0038] R 0 Each of the above can independently represent an aryl group having 6 to 20 carbon atoms or a cycloalkyl group having 5 to 6 carbon atoms, wherein any hydrogen atom in the aryl group having 6 to 20 carbon atoms or the cycloalkyl group having 5 to 6 carbon atoms can be independently substituted with a fluorine atom or an alkyl group having 1 to 20 carbon atoms.
[0039] R 1 Each of the following can independently represent a hydrogen atom, an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 5 to 6 carbon atoms, an arylalkyl group having 7 to 40 carbon atoms, or an alkyl group having 1 to 40 carbon atoms. In the aryl group having 6 to 20 carbon atoms, the cycloalkyl group having 5 to 6 carbon atoms, and the arylalkyl group having 7 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom or an alkyl group having 1 to 20 carbon atoms. In the alkylene group having 7 to 40 carbon atoms, any hydrogen atom can be substituted by a fluorine atom. Any -CH2- can be independently substituted by -O-, -CH=CH-, or a cycloalkylene group having 5 to 20 carbon atoms. In the alkyl group having 1 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom. Any -CH2- can be independently substituted by -O- or a cycloalkylene group having 5 to 20 carbon atoms.
[0040] R 2Each of the following can independently represent a hydroxyl group, an aryl group with 6 to 20 carbon atoms, a cycloalkyl group with 5 to 6 carbon atoms, an arylalkyl group with 7 to 40 carbon atoms, or an alkyl group with 1 to 40 carbon atoms. In the aryl group of the 6 to 20 carbon atoms, the cycloalkyl group with 5 to 6 carbon atoms, and the arylalkyl group with 7 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom or an alkyl group with 1 to 20 carbon atoms. In the alkylene group of the arylalkyl group with 7 to 40 carbon atoms, any hydrogen atom can be substituted by a fluorine atom. Any -CH2- can be independently substituted by -O-, -CH=CH-, or a cycloalkylene group with 5 to 20 carbon atoms. In the alkyl group with 1 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom. Any -CH2- can be independently substituted by -O- or a cycloalkylene group with 5 to 20 carbon atoms.
[0041] R 3 Each of the above refers to an alkylene group having 1 to 40 carbon atoms, wherein any -CH2- group may be independently substituted with -O- or a cycloalkylene group having 5 to 20 carbon atoms.
[0042] R 4 Each of the following can independently represent an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 5 to 6 carbon atoms, an arylalkyl group having 7 to 40 carbon atoms, or an alkyl group having 1 to 40 carbon atoms. In the aryl group having 6 to 20 carbon atoms, the cycloalkyl group having 5 to 6 carbon atoms, and the arylalkyl group having 7 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom or an alkyl group having 1 to 20 carbon atoms. In the alkylene group having 7 to 40 carbon atoms, any hydrogen atom can be substituted by a fluorine atom. Any -CH2- can be independently substituted by -O-, -CH=CH-, or a cycloalkylene group having 5 to 20 carbon atoms. In the alkyl group having 1 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom. Any -CH2- can be independently substituted by -O- or a cycloalkylene group having 5 to 20 carbon atoms.
[0043] R 5 Each can be independently represented as a hydroxyl group, hydrogen, or a crosslinking functional group of an alkenyl group having 2 to 40 carbon atoms, an alkyl group having 1 to 40 carbon atoms, a halogen, an acyl group having 1 to 15 carbon atoms, an alkoxy group having 1 to 15 carbon atoms, an oxime group having 1 to 15 carbon atoms, an amino group that may have a substituent, an amide group that may have a substituent, an aminooxy group that may have a substituent, or an ethylene alcohol residue having 2 to 15 carbon atoms, wherein the substituent in the amino and aminooxy groups has 1 to 15 carbon atoms;
[0044] p represents a real number greater than 1, and z represents a positive real number;
[0045] * indicates the location of the bond.
[0046] [2] The siloxane polymer according to [1] further has repeating units represented by formula (2) and / or formula (3);
[0047]
[0048] R 2 R in equation (4) of term [1] represents the relationship between R and R. 2 The same R 2 ;
[0049] x and y represent positive real numbers independently.
[0050] [3] The siloxane polymer according to [1] has repeating units represented by formula (2+4) and / or formula (4+2);
[0051]
[0052] R 2 R in equation (4) of term [1] represents the relationship between R and R. 2 The same R 2 ;
[0053] x and z represent positive real numbers independently.
[0054] [4] The siloxane polymer according to [1] or [3] has at least one repeating unit selected from the formula (4+2+3), (2+4+3), (2+3+4), (4+3+2), (3+4+2) and (3+2+4);
[0055]
[0056] R 2 R in equation (4) of term [1] represents the relationship between R and R. 2 The same R 2 ;
[0057] x, y, and z each represent a positive real number independently.
[0058] [5] The siloxane polymer according to any one of [1] to [4], wherein R 2 Each can be independently methyl or phenyl, R 4 Each of the following can be independently phenyl, isobutyl, cyclopentyl, cyclohexyl, trifluoropropyl, nonafluorohexyl or pentafluorophenyl.
[0059] [6] The siloxane polymer according to any one of [1] to [5], wherein the weight average molecular weight is 2,000 to 10,000,000.
[0060] [7] A siloxane polymer composition comprising a siloxane polymer according to any one of claims [1] to [6] and a solvent.
[0061] [8] A molded body is formed by hardening a siloxane polymer according to any one of claims [1] to [6] or a siloxane polymer composition according to claim [7].
[0062] [9] The molded article according to [8] wherein the haze value is less than 1%, the thermal decomposition temperature is in the range of 350°C to 450°C, and the coefficient of linear expansion is less than 200ppm.
[0063]
[10] The molded body according to item [8] has electrical insulation properties.
[0064]
[11] A molded body comprising: a hardened material formed by hardening a siloxane polymer according to any one of claims [1] to [6] or a siloxane polymer composition according to claim [7], and a substrate covered by the hardened material.
[0065]
[12] The molded body according to item
[11] , wherein the difference between the haze value of the molded body and the substrate is less than 1% and the coefficient of linear expansion is less than 200ppm.
[0066]
[13] The molded body according to
[11] has electrical insulation properties.
[0067] The effects of the invention
[0068] This invention provides a siloxane polymer containing silsesquioxane units and chain-like siloxane units in its main chain and having a cage-like silsesquioxane structure in its side chains, as well as a method for manufacturing the siloxane polymer. Furthermore, by coating a substrate with a composition obtained by dissolving the siloxane polymer in an organic solvent, and then peeling it off from the substrate after calcination, a highly transparent, flexible film with a low coefficient of thermal expansion can be obtained, utilizing the cohesive force (physical crosslinking) of the cage-like silsesquioxanes in the side chains. Detailed Implementation
[0069] The following details the embodiments of the present invention, but these are only examples (representative examples) of the embodiments of the present invention, and the present invention is not limited thereto in any way. Furthermore, the embodiments of the present invention can also be suitably combined.
[0070] Furthermore, the terms used in this specification are defined as follows. Alkyl and alkylene groups can be straight-chain or branched groups in any case. This is also true when any hydrogen in these groups is substituted with a halogen or cyclic group, or when any -CH2- is substituted with -O-, -CH=CH-, cycloalkylene, cycloalkenylene, phenylene, etc. The term "any" used in this invention indicates that not only the position but also the number is arbitrary. Moreover, when there are multiple groups, they can be substituted with different groups respectively. For example, when two -CH2- groups in an alkyl group are substituted with -O- and -CH=CH-, it indicates an alkoxyalkenyl or alkenoxyalkyl group. In this case, any group among alkoxy, alkenyl, alkenyl, and alkylene groups can be straight-chain or branched groups. Wherein, when it is stated that any -CH2- is substituted with -O-, there will not be multiple consecutive -CH2- substituted with -O-. That is, for example, -CH2-CH2- will not be substituted with -OO-.
[0071] One embodiment of the siloxane polymer of the present invention has repeating units represented by formulas (1) and (4), and the left and right ends are end groups represented by formulas (5L) and (5R). Furthermore, the term "left and right ends" refers to the appearance of the siloxane polymer of the present invention when represented by the structural formula.
[0072]
[0073] Equation (5L) represents the end base of the left-hand bond with the formula, Equation (5R) represents the end base of the right-hand bond with the formula, and A represents the following structure.
[0074]
[0075] The siloxane polymers of the present invention may further have repeating units represented by formula (2) and / or formula (3).
[0076]
[0077] Regarding the symbols in the formula, as described in items [1] to [2], they will be described in detail later.
[0078] The siloxane polymer of the present invention has repeating units represented by formulas (1) and (4), which constitute the "main chain". This main chain may further have repeating units represented by formulas (2) and / or (3). The two ends of the main chain are bonded with end groups represented by formulas (5L) and (5R). Formula (5L) represents the end group bonded to the left side of the formula, and (5R) represents the end group bonded to the right side. In these, A in formula (4) serves as a "side chain" bond.
[0079] The side chain represented by A has the following structure.
[0080]
[0081] 1. The "backbone" of siloxane polymers
[0082] The structure of the "main chain" of the siloxane polymer of the present invention is illustrated in view of it. The siloxane polymer of the present invention includes, for example, siloxane polymers having a main chain structure represented by the following formulas (main chain 1), (main chain 2-1) to (main chain 2-8), (main chain 3-1) to (main chain 3-12), (main chain 4-1) to (main chain 4-48) and (main chain 5-1) to (main chain 5-36). In these formulas, m represents a real number greater than 1, x', y' and z' each independently have the same meaning as x, y and z, and the meanings of other symbols are as described in the preceding items [1] to [2].
[0083]
[0084]
[0085]
[0086]
[0087]
[0088]
[0089]
[0090]
[0091]
[0092]
[0093]
[0094]
[0095]
[0096]
[0097]
[0098]
[0099]
[0100]
[0101] 2. Side chains of siloxane polymers
[0102] In this invention, the portion of the structure represented by A is referred to as a "side chain". Regarding R in side chain A... 4 and R 3 According to item [1].
[0103]
[0104] The side chain represented by A specifically includes the side chains of the structures (A-1) to (A-8) shown below.
[0105] In A, R 3 -CH2CH2CH2-, R 4 The structure is -CH2CH2CF3 (A-1).
[0106]
[0107] In A, R 3 -CH2CH2CH2-, R 4 The structure is that of a phenyl group (A-2).
[0108]
[0109] In A, R 3 -CH2CH2CH2-, R 4 It has the structure of cyclohexyl (A-3).
[0110]
[0111] In A, R 3 -CH2CH2CH2-, R 4 It has the structure of isobutyl (A-4).
[0112]
[0113] In A, R 3 -CH2CH2-, R 4 The structure is -CH2CH2CF3 (A-5).
[0114]
[0115] In A, R 3 -CH2CH2-, R 4 It has the structure of -phenyl (A-6).
[0116]
[0117] In A, R 3-CH2CH2-, R 4 It has the structure of cyclohexyl (A-7).
[0118]
[0119] In A, R 3 -CH2CH2-, R 4 It has the structure of isobutyl (A-8).
[0120]
[0121] The above lists R 3 Examples are -CH2CH2- or -CH2CH2CH2-, but R 3 The structure is not limited to these. As R... 3 Other preferred examples can be listed.
[0122] -CH2-、
[0123] -CH2CH2CH2CH2-、
[0124] -CH2CH2CH2CH2CH2-、
[0125] -CH2CH2CH2CH2CH2CH2-、
[0126] -CH2CH2CH2CH2CH2CH2CH2-、
[0127] -CH2CH2CH2CH2CH2CH2CH2CH2CH2-、
[0128] -CH2CH2CH2CH2CH2CH2CH2CH2CH2-、
[0129] -CH2CH2CH2CH2CH2CH2CH2CH2CH2CH2-、
[0130] -CH2CH2CH2CH2CH2CH2CH2CH2CH2CH2CH2-、
[0131] -CH2CH2CH2CH2CH2CH2CH2CH2CH2CH2CH2CH2-.
[0132] In addition to (A-1) to (A-8) mentioned above, R can be listed as another example. 4 The structure is nonafluorohexyl or pentafluorophenyl, or R can be listed. 4 It has a structure containing fluorinated polyether.
[0133] 3. Partial Structure of Siloxane Polymers
[0134] 3-1.(R 0 )
[0135] R 0 Independently represents an aryl group having 6 to 20 carbon atoms or a cycloalkyl group having 5 to 6 carbon atoms.
[0136] Examples of aryl groups with 6 to 20 carbon atoms include phenyl, naphthyl, anthraceneyl, phenanthrene, triphenylene, pyrene, etc. Phosyl, tetraphenyl, peryl, etc. Among these, phenyl, naphthyl, anthraceneyl, and phenanthryl are preferred, and phenyl, naphthyl, and anthraceneyl are more preferred.
[0137] Examples of cycloalkyl groups with 5 to 6 carbon atoms include cyclopentyl and cyclohexyl.
[0138] In the aryl group having 6 to 20 carbon atoms and the cycloalkyl group having 5 to 6 carbon atoms, any hydrogen atom may be independently substituted by a fluorine atom or an alkyl group having 1 to 20 carbon atoms.
[0139] R 0 Phenyl or cyclohexyl are preferred.
[0140] 3-2.(R 1 )
[0141] R 1 Independently representing a hydrogen atom, an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 5 to 6 carbon atoms, an arylalkyl group having 7 to 40 carbon atoms, or an alkyl group having 1 to 40 carbon atoms. Aryl groups having 6 to 20 carbon atoms and cycloalkyl groups having 5 to 6 carbon atoms can be listed with R. 0 The same base as the one described in the text.
[0142] Examples of arylalkyl groups having 7 to 40 carbon atoms include benzyl, phenethyl, diphenylmethyl, triphenylmethyl, 1-naphthylmethyl, 2-naphthylmethyl, 2,2-diphenylethyl, 3-phenylpropyl, 4-phenylbutyl, and 5-phenylpentyl.
[0143] Examples of alkyl groups having 1 to 40 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, sec-pentyl, isopentyl, tert-pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, dodecyl, and octadecyl.
[0144] In the aryl group of the 6-20 carbon groups, the cycloalkyl group of the 5-6 carbon groups, and the arylalkyl group of the 7-40 carbon groups, any hydrogen atom may be independently substituted by a fluorine atom or an alkyl group of the 1-20 carbon groups. In the alkylene group of the 7-40 carbon groups, any hydrogen atom may be substituted by a fluorine atom. Any -CH2- may be independently substituted by -O-, -CH=CH-, or a cycloalkylene group of the 5-20 carbon groups. In the alkyl group of the 1-40 carbon groups, any hydrogen atom may be independently substituted by a fluorine atom. Any -CH2- may be independently substituted by -O- or a cycloalkylene group of the 5-20 carbon groups.
[0145] R 1 Preferably, it is selected from hydrogen atoms, phenyl, cyclohexyl and alkyl groups having 1 to 5 carbon atoms, more preferably from alkyl groups having 1 to 5 carbon atoms.
[0146] 3-3.(R 2 R 5 )
[0147] R 2 R 5 Independently representing hydroxyl, aryl (6-20 carbons), cycloalkyl (5-6 carbons), arylalkyl (7-40 carbons), or alkyl (1-40 carbons).
[0148] Aryl groups with 6 to 20 carbon atoms and cycloalkyl groups with 5 to 6 carbon atoms can be listed with R. 0 The same as those described in the text.
[0149] As arylalkyl groups having 7 to 40 carbon atoms, examples include R 1 The same as those described in the text.
[0150] As alkyl groups having 1 to 40 carbon atoms, examples include R 1 The same as those described in the text.
[0151] In the aryl group of the 6-20 carbon groups, the cycloalkyl group of the 5-6 carbon groups, and the arylalkyl group of the 7-40 carbon groups, any hydrogen atom may be independently substituted by a fluorine atom or an alkyl group of the 1-20 carbon groups. In the alkylene group of the 7-40 carbon groups, any hydrogen atom may be substituted by a fluorine atom. Any -CH2- may be independently substituted by -O-, -CH=CH-, or a cycloalkylene group of the 5-20 carbon groups. In the alkyl group of the 1-40 carbon groups, any hydrogen atom may be independently substituted by a fluorine atom. Any -CH2- may be independently substituted by -O- or a cycloalkylene group of the 5-20 carbon groups.
[0152] R 2 R 5 Preferably, it is selected from phenyl, cyclohexyl and alkyl groups having 1 to 40 carbon atoms, and more preferably from alkyl groups having 1 to 5 carbon atoms.
[0153] 3-4.(p)
[0154] p represents a real number greater than or equal to 1. From a manufacturing point of view, it is preferable to have a value between 1 and 3000, and more preferably between 1 and 300.
[0155] 3-5. (x, y)
[0156] x is a value that depends on the amount of repeating units in the siloxane polymer having the structure of formula (2) contained in the main chain, and is 0 when the structure of formula (2) is not included. The content of repeating units of formula (2) varies depending on how much of the portion corresponding to the structure is loaded as a raw material for the siloxane polymer, and the physical properties of the siloxane polymer can be controlled by adjusting its amount. The preferred range of x is 0.5 to 10.
[0157] y is a repeating unit (the structure represented by formula (3)) contained in a certain proportion in the intermediate during the manufacturing stage of the siloxane polymer of the present invention, into which side chain A is introduced via an addition reaction (the method for manufacturing the siloxane polymer of the present invention will be described in detail later). Therefore, it is a value that depends on the proportion of the structure into which side chain A is introduced. The value of y is 0 when the structure into which side chain A is introduced is completely present in the -Si-H portion of the intermediate. The preferred range of y is 0.1 to 8.
[0158] 3-6.(z)
[0159] z is a value determined by the amount of A introduced into the side chain of the siloxane polymer. The preferred range for z is 0.2 to 5.
[0160] 4. Manufacturing methods of siloxane polymers
[0161] The method for manufacturing the siloxane polymer of the present invention will be described. First, a siloxane polymer with a structure in which the portion represented by A of the siloxane polymer of the present invention is substituted with hydrogen atoms is prepared. In this specification, the siloxane polymer is referred to as "intermediate (α)". A compound (β) corresponding to the structure of A is introduced into the -Si-H portion of the intermediate (α) by addition reaction, desorption reaction or substitution reaction.
[0162] For example, as shown in the following reaction formula, the compound represented by formula (β) can be produced by introducing the compound represented by formula (β) into the siloxane polymer intermediate represented by formula (α) via an addition reaction.
[0163]
[0164] The compound (β) corresponds to side chain A. In this example, the terminal double bond undergoes an addition reaction with the silicon atom of the siloxane polymer intermediate (α). In this example, the R of compound (β) 3The structure of ' becomes from R 3 The structure is formed by subtracting two carbons (the two carbons become -CH=CH2 and participate in the addition reaction).
[0165] The compounds (β) corresponding to the side chains A (A-1) to (A-8) are respectively (β-1) to (β-8).
[0166]
[0167] The examples listed illustrate the interaction between compound β and R. 3 The corresponding part is a compound β with structures of -CH=CH2 and -CH2CH=CH2, where an alkylene group with 4 to 12 carbon atoms is to be introduced as R. 3 In the case of , it corresponds to the following base.
[0168] -CH2CH2CH=CH2、
[0169] -CH2CH2CH2CH=CH2、
[0170] -CH2CH2CH2CH2CH=CH2、
[0171] -CH2CH2CH2CH2CH2CH=CH2、
[0172] -CH2CH2CH2CH2CH2CH2CH=CH2、
[0173] -CH2CH2CH2CH2CH2CH2CH2CH=CH2、
[0174] -CH2CH2CH2CH2CH2CH2CH2CH2CH=CH2,
[0175] -CH2CH2CH2CH2CH2CH2CH2CH2CH2CH=CH2,
[0176] -CH2CH2CH2CH2CH2CH2CH2CH2CH2CH2CH=CH2.
[0177] The siloxane polymers of the present invention can be manufactured by reacting these compounds (β) with siloxane polymer intermediates (α). A preferred example of the addition reaction is a hydrosilylation reaction using a Karstedt catalyst.
[0178] Additionally, when importing R 3 In the case of a -CH2- side chain, as (β), compounds such as the following can be selected as starting materials.
[0179]
[0180] Additionally, when importing R 3 In the case of a -O- side chain, the compound represented by compound (β) can be introduced into the siloxane polymer intermediate (α) by a dehydrogenation reaction as shown in the following reaction formula.
[0181]
[0182] The compound (β) OH Corresponding to side chain A, in the example described, the terminal silanol group undergoes a dehydrogenation reaction in the presence of a hydrogenated silane alkyl group of the siloxane polymer intermediate (α) and a boron compound catalyst.
[0183] Alternatively, it can be done via R 2 Part of it is a hydroxyl-containing siloxane polymer intermediate (α) OH The siloxane polymers of the present invention are produced by desorption or substitution reactions of the compound (β) with the compound (β).
[0184]
[0185] The compound (β) H Corresponding to side chain A, in the example described, the terminal hydrogenated silane alkyl group in the siloxane polymer intermediate (α) OH The silanol group of the compound undergoes a dehydrogenation reaction with a boron compound catalyst.
[0186]
[0187] The compound (β) OH Corresponding to side chain A, in this example, the terminal silanol group corresponds to the siloxane polymer intermediate (α). OH The silanol group of ) undergoes dehydration condensation under acidic conditions.
[0188]
[0189] The compound (β) Cl Corresponding to side chain A, in this example, the terminal chlorosilane and siloxane polymer intermediate (α) OH The silanol group undergoes a dehydrochlorination reaction. This reaction can be readily promoted by adding compounds with amino groups, such as triethylamine (TEA), or basic organic compounds.
[0190] 4-1-a. Siloxane polymer intermediates (α)
[0191] The siloxane polymer intermediate (α) (hereinafter referred to as "intermediate (α)") is used as a raw material for manufacturing the siloxane polymer of the present invention. Alternatively, as described later, intermediate (α) can also be manufactured by converting the hydrogen atoms of Si-H into silanol groups in the presence of a transition metal catalyst. OH The intermediate (α) is a raw material. Furthermore, the intermediate (α) itself is not merely an "intermediate," but becomes a material that can be hardened and used. Therefore, the intermediate (α) can also be understood as a useful invention.
[0192] Here, in the case where the intermediate (α) is understood as the invention, it is redefined as a siloxane polymer (α') as shown below.
[0193] [1'] A siloxane polymer (α') having formula (1), formula (2) and formula (4) H The repeating unit represented by ) has end bases represented by equations (5L) and (5R) on both sides;
[0194]
[0195] Equation (5L) represents the terminal base of the left-hand bond with the equation, and (5R) represents the terminal base of the right-hand bond with the equation;
[0196] R 0 Each of the above can independently represent an aryl group having 6 to 20 carbon atoms or a cycloalkyl group having 5 to 6 carbon atoms, wherein any hydrogen atom in the aryl group having 6 to 20 carbon atoms or the cycloalkyl group having 5 to 6 carbon atoms can be independently substituted with a fluorine atom or an alkyl group having 1 to 20 carbon atoms.
[0197] R 1 Each of the following can independently represent a hydrogen atom, an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 5 to 6 carbon atoms, an arylalkyl group having 7 to 40 carbon atoms, or an alkyl group having 1 to 40 carbon atoms. In the aryl group having 6 to 20 carbon atoms, the cycloalkyl group having 5 to 6 carbon atoms, and the arylalkyl group having 7 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom or an alkyl group having 1 to 20 carbon atoms. In the alkylene group having 7 to 40 carbon atoms, any hydrogen atom can be substituted by a fluorine atom. Any -CH2- can be independently substituted by -O-, -CH=CH-, or a cycloalkylene group having 5 to 20 carbon atoms. In the alkyl group having 1 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom. Any -CH2- can be independently substituted by -O- or a cycloalkylene group having 5 to 20 carbon atoms.
[0198] R 2Each of the following can independently represent a hydroxyl group, an aryl group with 6 to 20 carbon atoms, a cycloalkyl group with 5 to 6 carbon atoms, an arylalkyl group with 7 to 40 carbon atoms, or an alkyl group with 1 to 40 carbon atoms. In the aryl group of the 6 to 20 carbon atoms, the cycloalkyl group with 5 to 6 carbon atoms, and the arylalkyl group with 7 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom or an alkyl group with 1 to 20 carbon atoms. In the alkylene group of the arylalkyl group with 7 to 40 carbon atoms, any hydrogen atom can be substituted by a fluorine atom. Any -CH2- can be independently substituted by -O-, -CH=CH-, or a cycloalkylene group with 5 to 20 carbon atoms. In the alkyl group with 1 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom. Any -CH2- can be independently substituted by -O- or a cycloalkylene group with 5 to 20 carbon atoms.
[0199] R 5 Each can be independently represented as a hydroxyl group, hydrogen, or a crosslinking functional group of an alkenyl group having 2 to 40 carbon atoms, an alkyl group having 1 to 40 carbon atoms, a halogen, an acyl group having 1 to 15 carbon atoms, an alkoxy group having 1 to 15 carbon atoms, an oxime group having 1 to 15 carbon atoms, an amino group that may have a substituent, an amide group that may have a substituent, an aminooxy group that may have a substituent, or an ethylene alcohol residue having 2 to 15 carbon atoms, wherein the substituent in the amino and aminooxy groups has 1 to 15 carbon atoms;
[0200] p represents a real number greater than 1, and x and z independently represent positive real numbers;
[0201] * indicates the location of the bond.
[0202] [2'] The siloxane polymer (α') according to item [1'] has the formula (2+4) H ) and / or formula (4) H +2) represents the repeating unit;
[0203]
[0204] R 2 This indicates the expression (4) in the [1'] term. H R in ) 2 The same R 2 ;
[0205] x independently represents 0 or a positive real number, and z independently represents a positive real number.
[0206] [3'] The siloxane polymer (α') according to item [1'] or [2'], wherein R 2 Each can be methyl or phenyl, independently.
[0207] [4'] The siloxane polymer (α') according to any one of [1'] to [3'], wherein the weight average molecular weight is 2,000 to 10,000,000.
[0208] [5'] A siloxane polymer composition comprising a siloxane polymer (α') according to any one of [1'] to [4'] and a solvent.
[0209] [6'] A molded body is formed by hardening a siloxane polymer (α') according to any one of [1'] to [4'] or a siloxane polymer composition according to [5'].
[0210] [7'] The molded body according to [6'] has electrical insulation properties.
[0211] [8'] A molded body comprising: a hardened material formed by hardening a siloxane polymer (α') according to any one of [1'] to [4'] or a siloxane polymer composition according to [5'], and a substrate covered by the hardened material.
[0212] [9'] The molded body according to [8'] has electrical insulation properties.
[0213] The invention of the siloxane polymer (α') not only provides a siloxane polymer (α') containing silsesquioxane units and chain siloxane units in the main chain and a method for manufacturing the siloxane polymer (α'), but also allows for the production of a hardened film with excellent heat resistance, where Si-H groups serve as crosslinking points, by coating a substrate with a composition in which the siloxane polymer (α') is dissolved in an organic solvent and then heat-curing it. Furthermore, the siloxane polymer (α') can introduce functional groups into the Si-H groups, thus making it useful as an intermediate for manufacturing siloxane polymers with highly controllable heat resistance or mechanical properties.
[0214] 4-1-b. Method for manufacturing intermediate (α)
[0215] Many examples of methods for producing intermediate (α) are known, for instance, by reacting the following compounds in the presence of an acid catalyst. Compounds With compounds <c>Obtained through equilibrium polymerization. Compound< / c> This can be achieved by making the following compounds <d>With compounds <e>or compounds <f>The reaction is followed by hydrolysis to obtain the product (see, for example, paragraph 0032 of Japanese Patent Application Publication No. 2006-022207). However, the specific structure of the intermediate (α) or the siloxane polymer (α') is not yet known.
[0216]
[0217] 4-2. Intermediate (α) OH Manufacturing method of )
[0218] Regarding the manufacturing intermediate (α) OH The method can be used, for example, to manufacture the intermediate (α) by converting it to a silanol group in the presence of a transition metal catalyst.
[0219]
[0220] 4-3. Methods for manufacturing compound (β)
[0221] The method for manufacturing compound (β) is also described.
[0222] Compound (β) can be produced by reacting compound (β-0) with allyltrichlorosilane.
[0223]
[0224] Compound (β) OH It can be produced by hydrolyzing the compound (β-0).
[0225]
[0226] Compound (β) Cl It can be produced by reacting compound (β-0) with tetrachlorosilane.
[0227]
[0228] Compound (β) H It can be produced by reacting compound (β-0) with trichlorosilane.
[0229]
[0230] There are many known methods for manufacturing the compound (β-0), such as by hydrolyzing and polycondensing trifluoropropyltrimethoxysilane in the presence of an alkali metal hydroxide.
[0231]
[0232] These manufacturing methods are described, for example, in paragraph 32 of Japanese Patent Application Publication No. 2005-15738.
[0233] 5. Solvent
[0234] The siloxane polymer of the present invention can be used as a siloxane polymer composition containing a solvent. This solvent is preferably one that can dissolve the siloxane polymer without condensing with crosslinking silicon compounds or crosslinking compounds. Examples of such solvents include hydrocarbon solvents such as hexane or heptane, aromatic hydrocarbon solvents such as benzene, toluene, and xylene, ether solvents such as diethyl ether, tetrahydrofuran (THF), and dioxane, halogenated hydrocarbon solvents such as dichloromethane and carbon tetrachloride, and ester solvents such as ethyl acetate. The solvent can be a single solvent or two or more solvents. For example, from the viewpoint of coatability, the content of the solvent is preferably 20-80% by mass, more preferably 30-70% by mass, and even more preferably 40-60% by mass.
[0235] 6. Calcinated products and membranes
[0236] By calcining a siloxane polymer composition containing the siloxane polymer or solvent of the present invention, a calcined product with high transparency and low coefficient of thermal expansion can be obtained. The calcination temperature is preferably 150–250°C. The calcined product can be used as a membrane.
[0237] Specifically, calcination simply involves heating the substrate after the siloxane polymer composition has been applied to it using an oven or similar device.
[0238] There are no particular limitations regarding the calcination temperature and time, if the siloxane polymer can be formed into a film (self-supporting film). After cooling, the calcined siloxane polymer can be peeled off from the substrate as a film.
[0239] There are no particular limitations on the substrate if it is one that can withstand the calcination temperature and allows the film formed on the substrate to be peeled off and removed as a self-supporting film. Examples of substrates that can be used include glass substrates such as quartz, barium borosilicate glass, and aluminum borosilicate glass; calcium fluoride substrates; metal oxide substrates such as indium tin oxide (ITO); ceramic substrates; plastic films such as polycarbonate (PC) films, silicone films, polyethylene terephthalate (PET) films, polyethylene naphthalate (PEN) films, cyclic olefin polymer (COP) films, polypropylene films, polyethylene films, acrylic polymer films, polyvinyl alcohol films, triacetyl cellulose films, and polyimide (PI) films; fluoropolymer substrates such as polytetrafluoroethylene (PTFE) and perfluoroalkoxyalkane (PFA); laminated substrates coated with fluoropolymers on glass or the like; and metal substrates such as SUS and copper.
[0240] Example
[0241] The present invention will be described in more detail below with reference to embodiments, but the scope of the present invention is not limited thereto.
[0242] The measurements in the examples were performed as follows.
[0243] GPC (Gel Permeation Chromatography)
[0244] <Measurement Conditions>
[0245] Tube column: Showa Denko (Co., Ltd.) manufactured Shodex KF-804L 300mm × 8.0mm
[0246] Showa Denko Co., Ltd. manufactures Shodex KF-805L 300mm x 8.0mm 2-in-line series connectors.
[0247] Moving phase: THF
[0248] Flow rate: 1.0 ml / min
[0249] Temperature: 40℃
[0250] Detector: RI
[0251] Molecular weight standard sample: Polymethyl methacrylate (PMMA) resin with a known molecular weight.
[0252] DMA (Dynamic Mechanical Analysis) dynamic viscoelasticity measurement
[0253] <Measurement Conditions>
[0254] Hitachi High-Tech Science DMS6100
[0255] 5℃ / min, sample area 10mm×1mm
[0256] Load 10mN, measurement frequency 10Hz
[0257] • TMA (Thermomechanical Analysis)
[0258] <Measurement Conditions>
[0259] Hitachi High-Tech Science SS / TMA6100
[0260] Tensile mode, 10℃ / min, length 20mm, cross-sectional area 0.3mm² 2
[0261] Load 9.8mN
[0262] ·TG-DTA thermogravimetric analysis
[0263] <Measurement Conditions>
[0264] Measurement Apparatus: Seiko Instruments EXSTAR 6000TG / DTA6300
[0265] Pot: Pt
[0266] Standard sample: Alumina (10 mg)
[0267] Sample weight: Approximately 10 mg
[0268] Temperature program: 25℃~800℃
[0269] Heating rate: 10℃ / min
[0270] • Total light transmittance: Total light transmittance was measured using a haze meter NDH5000 (manufactured by Nippon Denshoku Kogyo Co., Ltd.) based on Japanese Industrial Standard (JIS) K 7361-1.
[0271] • HAZE: HAZE (darkness, haze) was measured using a haze meter NDH5000 (manufactured by Nippon Denshoku Kogyo Co., Ltd.) based on JIS K7136.
[0272] Glass transition temperature: The temperature at which the loss elastic coefficient (E”) peaks in dynamic viscoelasticity measurements using DMA.
[0273] • Crosslinking density: The crosslinking density is calculated according to the formula (1).
[0274] n=E' / 3RT······(1)
[0275] In equation (1), n: crosslinking density (mol / m 3 E': Storage elasticity coefficient (Pa), R: Gas constant (Pa·m) 3 (K·mol)), T: temperature (K)
[0276] • Coefficient of Thermal Expansion (CTE): Measured by TMA. The coefficient of thermal expansion is calculated based on the results of the first scan (first heating, heating rate: 10℃ / min) within a temperature range of 40℃ to 250℃.
[0277] Thermal decomposition temperature (T) d5 ): Determined by TG-DTA. Temperature at which weight decreases by 5%.
[0278] • Elastic modulus: Determined using a Tensilon RTF-1310 universal testing machine (manufactured by A&D) through tensile tests at a tensile speed of 5 mm / min and room temperature. The test specimens were prepared using an 8-gauge dumbbell, and the tangent to the maximum slope of the stress / strain curve before plastic deformation of the membrane was used.
[0279] • Maximum stress: Determined using a Tensilon RTF-1310 universal testing machine (manufactured by A&D) through a tensile test at a tensile speed of 5 mm / min and at room temperature. The test specimen was prepared using a No. 8 dumbbell, and the maximum stress was measured before the specimen fractured.
[0280] • Volume resistivity: The volume resistivity was calculated based on the resistance value when a voltage of 250V was applied, using a Femto Picoammeter B2981A, controller GP-32, controller GP-HV, and test fixture N1259A (manufactured by Keysight Technologies, Inc.). For the test pieces, a siloxane polymer film was formed on a Cr-plated substrate using a spin coater and calcined, followed by an Al-plated substrate.
[0281] The siloxane polymers were prepared according to the reaction formulas shown below (Examples 1-3), and their physical properties were evaluated. The obtained siloxane polymers were used to prepare solutions according to the compositions shown in Table 3, coated onto a substrate coated with fluororesin, heated at a temperature above 180°C for more than 3 hours, cooled, and then peeled off from the substrate to obtain a self-supporting film.
[0282]
[0283] The relationships between x, y, and z in the intermediate (α), compound (β-1), and product of Examples 1-3 are shown in Table 1.
[0284] Table 1
[0285]
[0286] [Example 1]
[0287] 5 g of compound (α), 1.5 g of compound (β-1), and 15.0 g of ethyl acetate were added to a 100 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 2.1 μL of Pt-VTSC×3.0 (Umicore Japan) was added at 70 °C, and the mixture was stirred at reflux for 5 hours. After cooling to room temperature, 2.8 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was separated by filtration, and the filtrate was concentrated at 50 °C. Propylene glycol monomethyl ether acetate (PGMEA) was added to the concentrate, and ethyl acetate was removed by concentration under reduced pressure, thereby obtaining 10.9 g of solution (A) with a solid content of 60%.
[0288] The molecular weight of (A) was determined using GPC. The weight-average molecular weight (Mw) was 47,000, and the polydispersity (Mw / Mn) was 4.0. 1 H-NMR ( 1 H-NMR) 29 The average values (x, y, z) were calculated from Si-NMR measurements. The average value of x was 3.2, the average value of y was 0.41, and the average value of z was 0.39.
[0289] ( 1 (H-NMR measurement results)
[0290] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.17~7.66(Ph), 4.65~4.74(Si-H), 2.34(CF3CH2), 1.51~1.6 0(CH2), 1.02(CF3CH2CH2), 0.65~0.87(CH2), 0.27~0.41(O3SiMe), -0.04~0.13(O2SiMe2).
[0291] ( 29 (Si-NMR measurement results)
[0292] 29 Si-NMR (99MHz, CO(CD3)2) δ: 9.9, -21.9~-18.3, -37.6.9~-34.8, -65.0~-64.0, -67.2~-66.8, -67.6~-67.2, -70.1, -79.6~-78.6
[0293] [Example 2]
[0294] 5 g of compound (α), 2.2 g of compound (β-1), and 16.0 g of ethyl acetate were added to a 100 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 2.1 μL of Pt-VTSC×3.0 (manufactured by Umicore Japan) was added at 70 °C, and the mixture was stirred at reflux temperature for 5 hours. After cooling to room temperature, 5.0 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was filtered to separate the solids, and the filtrate was concentrated at 50 °C. PGMEA was added to the concentrate, and ethyl acetate was removed by concentration under reduced pressure, thereby obtaining 11.6 g of a (B) solution with a solid content of 60%.
[0295] The molecular weight of (B) was determined using GPC. The weight-average molecular weight Mw was 128,000, and the polydispersity Mw / Mn = 4.0. 1 H-NMR, 29 The average values (x, y, z) were calculated from Si-NMR measurements. The average value of x was 3.2, the average value of y was 0.24, and the average value of z was 0.56.
[0296] ( 1 (H-NMR measurement results)
[0297] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.17~7.65(Ph), 4.64~4.82(Si-H), 2.33(CF3CH2), 1.49~1.5 8(CH2), 1.01(CF3CH2CH2), 0.61~0.89(CH2), 0.26~0.39(O3SiMe), -0.06~0.12(O2SiMe2).
[0298] ( 29 (Si-NMR measurement results)
[0299] 29 Si-NMR (99MHz, CO(CD3)2) δ: 9.9, -21.9~-18.5, -37.6.9~-34.8, -65.0~-64.0, -66.4~-66.1, -67.7~-67.2, -70.1, -79.6~-78.6
[0300] [Example 3]
[0301] 5 g of compound (α), 4.4 g of compound (β-1), and 22.0 g of ethyl acetate were added to a 100 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 6.0 μL of Pt-VTSC×3.0 (manufactured by Umicore Japan) was added at 70 °C, and the mixture was stirred at reflux temperature for 5 hours. After cooling to room temperature, 8.0 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was filtered to separate the filtrate, and the filtrate was concentrated at 50 °C. PGMEA was added to the concentrate, and ethyl acetate was removed by concentration under reduced pressure, thereby obtaining 15.5 g of a (C) solution with a solid content of 60%.
[0302] The molecular weight of (C) was determined using GPC. The weight-average molecular weight (Mw) was 163,000, and the polydispersity (Mw / Mn) was 4.8. 1 H-NMR, 29 The average values (x, y, z) were calculated from Si-NMR measurements. The average value of x was 2.1, the average value of y was 0.79, and the average value of z was 1.21.
[0303] ( 1 (H-NMR measurement results)
[0304] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.23~7.69(Ph), 4.67~4.86(Si-H), 2.36(CF3CH2), 1.52~1.6 2(CH2), 1.04(CF3CH2CH2), 0.64~0.89(CH2), 0.29~0.43(O3SiMe), 0.00~0.17(O2SiMe2).
[0305] ( 29 (Si-NMR measurement results)
[0306] 29 Si-NMR (99MHz, CO(CD3)2) δ: 9.9, -21.9~-18.3, -36.3~-34.7, -65.0~-64.0, -66.1~-66.3, -67.9~-67.2, -70.1, -79.4~-78.9
[0307] [Example 4]
[0308] Use (β-5) as compound (β).
[0309]
[0310] The following siloxane polymer can be obtained by the same manufacturing method as in Example 1.
[0311]
[0312] The siloxane polymers were prepared according to the reaction formulas shown below (Examples 4-9), and their physical properties were evaluated. The obtained siloxane polymers were used to prepare solutions according to the compositions shown in Tables 3-4, coated onto a substrate coated with fluororesin, heated at a temperature above 180°C for more than 3 hours, cooled, and then the film was peeled off from the substrate to obtain a self-supporting film.
[0313]
[0314] The relationships between x, y, and z in the intermediate (α), compound (β-2), and products of Examples 4–9 are shown in Table 2.
[0315] Table 2
[0316]
[0317] [Example 4]
[0318] 5 g of compound (α), 1.3 g of compound (β-2), and 14.7 g of THF were added to a 50 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 2.1 μL of Pt-VTSC×3.0 (manufactured by Umicore Japan) was added at 60 °C, and the mixture was stirred at reflux for 3 hours. Then, another 2.1 μL of Pt-VTSC×3.0 was added, and the mixture was stirred at reflux for another 3 hours. After cooling to room temperature, 1.8 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was separated by filtration, and the filtrate was concentrated at 50 °C. The concentrated solution was added dropwise to 200 mL of heptane to obtain 4.2 g of a white polymer precipitate.
[0319] The molecular weight of the polymer was determined using GPC, and the results showed a weight-average molecular weight (Mw) of 115,000 and a polydispersity (Mw / Mn) of 2.1. 1 The average values of (x, y, z) were calculated by H-NMR. The average value of x was 3.6, the average value of y was 0.48, and the average value of z was 0.32.
[0320] ( 1 (H-NMR measurement results)
[0321] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.17~7.66(Ph), 4.65~4.74(Si-H), 1.51~1.60(CH2), 0.65~0.87(CH2), 0.27~0.41(O3SiMe), -0.04~0.13(O2SiMe2).
[0322] [Example 5]
[0323] 5.25 g of compound (α), 1.33 g of compound (β-2), and 15.8 g of THF were added to a 50 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 3.0 μL of Pt-VTSC×3.0 (manufactured by Umicore Japan) was added at 60 °C, and the mixture was stirred at reflux for 3 hours. Another 3.0 μL of Pt-VTSC×3.0 was added, and the mixture was stirred at reflux for another 4 hours. After cooling to room temperature, 2.5 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was separated by filtration, and the filtrate was concentrated at 50 °C. The concentrated solution was added dropwise to 200 mL of heptane to obtain 4.7 g of a white polymer precipitate.
[0324] The molecular weight of the polymer was determined using GPC, and the results showed a weight-average molecular weight (Mw) of 88,000 and a polydispersity (Mw / Mn) of 2.4. 1 The average values of (x, y, z) were calculated by H-NMR. The average value of x was 3.3, the average value of y was 0.68, and the average value of z was 0.42.
[0325] ( 1 (H-NMR measurement results)
[0326] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.17~7.66(Ph), 4.65~4.74(Si-H), 1.51~1.60(CH2), 0.65~0.87(CH2), 0.27~0.41(O3SiMe), -0.04~0.13(O2SiMe2).
[0327] [Example 6]
[0328] 30 g of compound (α), 7.6 g of compound (β-2), and 87.8 g of THF were added to a 200 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 14 μL of Pt-VTSC×3.0 (manufactured by Umicore Japan) was added at 60 °C, and the mixture was stirred at reflux for 3.5 hours. Another 14 μL of Pt-VTSC×3.0 was added, and the mixture was stirred at reflux for another 3 hours. After cooling to room temperature, 7.5 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was separated by filtration, and the filtrate was concentrated at 50 °C. The concentrated solution was added dropwise to 1.5 L of heptane to obtain 33.7 g of a white polymer precipitate.
[0329] The molecular weight of the polymer was determined using GPC, and the results showed a weight-average molecular weight (Mw) of 100,000 and a polydispersity (Mw / Mn) of 2.9. 1 The average values of (x, y, z) were calculated by H-NMR. The average value of x was 2.8, the average value of y was 1.12, and the average value of z was 0.48.
[0330] ( 1 (H-NMR measurement results)
[0331] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.17~7.66(Ph), 4.65~4.74(Si-H), 1.51~1.60(CH2), 0.65~0.87(CH2), 0.27~0.41(O3SiMe), -0.04~0.13(O2SiMe2).
[0332] [Example 7]
[0333] 6 g of compound (α), 0.9 g of compound (β-2), and 16.1 g of THF were added to a 50 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 2.5 μL of Pt-VTSC×3.0 (manufactured by Umicore Japan) was added at 60 °C, and the mixture was stirred at reflux temperature for 1.5 hours. After cooling to room temperature, 2.5 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was filtered to separate the precipitate, and the filtrate was concentrated at 50 °C. The concentrated solution was added dropwise to 300 mL of heptane to obtain 6.1 g of a white polymer precipitate.
[0334] The molecular weight of the polymer was determined using GPC, and the results showed a weight-average molecular weight (Mw) of 112,000 and a polydispersity (Mw / Mn) of 2.6. 1 The average values of (x, y, z) were calculated by H-NMR. The average value of x was 2.8, the average value of y was 1.33, and the average value of z was 0.27.
[0335] ( 1 (H-NMR measurement results)
[0336] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.17~7.66(Ph), 4.65~4.74(Si-H), 1.51~1.60(CH2), 0.65~0.87(CH2), 0.27~0.41(O3SiMe), -0.04~0.13(O2SiMe2).
[0337] [Example 8]
[0338] 6 g of compound (α), 2.0 g of compound (β-2), and 19.5 g of THF were added to a 50 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 3.3 μL of Pt-VTSC×3.0 (manufactured by Umicore Japan) was added at 60 °C, and the mixture was stirred at reflux for 3 hours. Another 3.3 μL of Pt-VTSC×3.0 was added, and the mixture was stirred at reflux for another 2 hours. After cooling to room temperature, 2.5 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was separated by filtration, and the filtrate was concentrated at 50 °C. The concentrated solution was added dropwise to 300 mL of heptane to obtain 7.4 g of a white polymer precipitate.
[0339] The molecular weight of the polymer was determined using GPC, and the results showed a weight-average molecular weight (Mw) of 92,000 and a polydispersity (Mw / Mn) of 2.9. 1 The average values of (x, y, z) were calculated by H-NMR. The average value of x was 2.8, the average value of y was 0.91, and the average value of z was 0.269.
[0340] ( 1 (H-NMR measurement results)
[0341] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.17~7.66(Ph), 4.65~4.74(Si-H), 1.51~1.60(CH2), 0.65~0.87(CH2), 0.27~0.41(O3SiMe), -0.04~0.13(O2SiMe2).
[0342] [Example 9]
[0343] 6 g of compound (α), 1.4 g of compound (β-2), and 17.9 g of THF were added to a 50 mL four-necked round-bottom flask. A thermometer, reflux tube, stirrer, and oil bath were set up, and the mixture was stirred while nitrogen was introduced. 2.7 μL of Pt-VTSC×3.0 (manufactured by Umicore Japan) was added at 60 °C, and the mixture was stirred at reflux temperature for 7 hours. After cooling to room temperature, 2.5 g of activated carbon was added, and the mixture was stirred overnight. The activated carbon was separated by filtration, and the filtrate was concentrated at 50 °C. The concentrated solution was added dropwise to 200 mL of heptane to obtain 5.4 g of a white polymer precipitate.
[0344] The molecular weight of the polymer was determined using GPC, and the results showed a weight-average molecular weight (Mw) of 116,000 and a polydispersity (Mw / Mn) of 2.8. 1 The average values of (x, y, z) were calculated by H-NMR. The average value of x was 3.8, the average value of y was 0.78, and the average value of z was 0.42.
[0345] ( 1 (H-NMR measurement results)
[0346] 1 H-NMR (400MHz, CO(CD3)2)δ: 7.17~7.66(Ph), 4.65~4.74(Si-H), 1.51~1.60(CH2), 0.65~0.87(CH2), 0.27~0.41(O3SiMe), -0.04~0.13(O2SiMe2).
[0347] [Comparative Example 1]
[0348] A polymer solution containing formulas (1), (2), and (3) described in items [1] and [2] (excluding formula (4)) is coated onto a substrate coated with fluororesin. After heating at a temperature above 180°C for more than 3 hours, the film is peeled off from the substrate after cooling to obtain a self-supporting film.
[0349] [Comparative Example 2]
[0350] Add MKC to the polymer solution TM Silicate MS51 (Mitsubishi Chemical Co., Ltd., trade name) and dibutyltin dilaurate (DBTL) were coated onto an Afrex (AGC Co., Ltd., trade name) substrate. The substrate was then calcined at 70°C for 10 minutes, at 90°C for 1 hour, at 110°C for 40 minutes, and at 220°C for 2 hours. After cooling, the film was peeled off from the substrate to obtain a self-supporting film.
[0351] [Comparative Example 3]
[0352] After mixing and stirring the compound (β-5) in a polymer solution containing formulas (1), (2), and (3) as described in items [1] and [2] (excluding formula (4)), the mixture was coated onto a substrate coated with fluororesin and calcined at 70°C for 10 minutes, at 90°C for 1 hour, at 110°C for 40 minutes, and at 220°C for 2 hours. However, the mixture became cloudy, had low self-retention properties, and could not produce a transparent film.
[0353] The results of Examples 1 to 9 and Comparative Examples 1 to 3 are summarized in Tables 3 to 4.
[0354] Table 3
[0355]
[0356] Table 4
[0357]
[0358] The volume resistivity (Ω·cm) of Example 6 and Comparative Examples 1-2 was measured, and the results are shown in Table 5.
[0359] Table 5
[0360]
[0361] [Example 10]
[0362] Use (β-3) as compound (β).
[0363]
[0364] The following siloxane polymer can be obtained by the same manufacturing method as in Example 1.
[0365]
[0366] The following examples relate to siloxane polymers (α'). The siloxane polymers were manufactured according to the reaction formulas shown below (Examples 1' to 7').
[0367]
[0368] The synthesis conditions of Examples 1' to 7' are shown in Table 6, and the weight-average molecular weight, polydispersity, and x and y relationship of the generated compound (α') are shown in Table 7.
[0369] Table 6
[0370]
[0371] Table 7
[0372] 1' a'-1 24,700 2.0 88 x = 0, y = average 3.7 2' a'-2 31,800 1.7 27.5 x = average 3.2, y = average 0.8 3' a'-3 28,100 1.7 29 x = average 2.1, y = average 2.0 4' a'-4 74,000 2.0 19 x = average 3.6, y = average 0.8 5' a'-5 59,400 2.0 41 x = average 3.2, y = average 1.1 6' a'-6 68,000 2.1 121 x = average 2.8, y = average 1.6 7' a'-7 91,000 2.4 36 x = average 3.8, y = average 1.2
[0373] [Example 1]
[0374] Add the compound to a 300mL four-necked round-bottom flask< / f> < / e> < / d> 100g, compound 0g, compound <c>30.4 g of hexamethyldisiloxane (MM) as an end-sealing material and 1.20 g of methyldisiloxane were diluted with a 4:1 mixture of toluene and 4-methyltetrahydroxypyran to achieve a monomer concentration of 50% by weight. A thermometer, reflux pipe, and oil bath were set up, and nitrogen gas was introduced while stirring with a stirrer. 6.08 g of methanesulfonic acid was added as an acid catalyst, and the reaction was carried out at 75°C for 2 hours. After cooling to below 50°C, the acid in the system was removed by washing with water. Then, the acid was completely removed using Kyoward 500SN adsorbent (produced by Kyowa Chemical Industry Co., Ltd.), and heptane was used as a poor solvent to precipitate the solid. The precipitated solid was dried under reduced pressure at 80°C for 5 hours to obtain 88 g of a white compound (α'-1).
[0375] The molecular weight of (α'-1) was determined using GPC, and the weight-average molecular weight Mw was 24,700, with a polydispersity Mw / Mn = 2.0. 1 H-NMR, 29 The average values of (x, y) were calculated from Si-NMR measurements, with x averaging 0 and y averaging 3.7.
[0376] [Examples 2' to 7']
[0377] Except for the reaction conditions shown in Table 6, compound (α'-7) was obtained from compound (α'-2) according to Example 1'. The weight-average molecular weight, polydispersity, x, and y of each compound were determined using the method of Example 1, and the results are shown in Table 7.
[0378] The obtained siloxane polymer was used to prepare a self-supporting film using the method shown below, and its physical properties were evaluated (Examples 8' to 10').
[0379] [Example 8']
[0380] For siloxane polymers, a solution is prepared according to the composition shown in Table 8, coated onto a substrate coated with fluororesin, heated at a temperature above 180°C for more than 3 hours, cooled, and then peeled off from the substrate to obtain a self-supporting film.
[0381] [Example 9' to Example 10']
[0382] In addition to the composition shown in Table 8, a self-supporting membrane was obtained according to Example 8'.
[0383] [Comparative Example 1', Comparative Example 2']
[0384] For siloxane polymers, MKC is added according to the composition shown in Table 8. TM Silicate MS51 (Mitsubishi Chemical Co., Ltd., trade name) and dibutyltin dilaurate (DBTL) were coated onto an Afrex (AGC Co., Ltd., trade name) substrate. The substrate was then calcined at 70°C for 10 minutes, at 90°C for 1 hour, at 110°C for 40 minutes, and at 220°C for 2 hours. After cooling, the film was peeled off from the substrate to obtain a self-supporting film.
[0385] "Comparative Example 1" is the same as "Comparative Example 2" and is disclosed again for comparison with Examples 8' to 10'.
[0386] The results of Examples 8' to 10' and Comparative Examples 1' and 2' are summarized in Table 8.
[0387] Table 8
[0388]
[0389] The volume resistivity (Ω·cm) of Example 9' and Comparative Example 1' was measured. The results are shown in Table 9 ("Comparative Example 1'" is the same as "Comparative Example 2" and is disclosed again for comparison with the volume resistivity of Example 9').
[0390] Table 9
[0391]
[0392] Industrial availability
[0393] The film obtained by calcining the siloxane polymer of the present invention is a material that combines heat resistance, transparency, and a low coefficient of thermal expansion, and is particularly preferably used as an electronic component. Furthermore, the siloxane polymer (α') of the present invention can be used as an intermediate in the manufacture of the siloxane polymer, and the cured film of the siloxane polymer (α') itself also exhibits excellent heat resistance, thus making it particularly preferably used as an electronic component.< / c>
Claims
1. A siloxane polymer having repeating units represented by formulas (1) and (4), with end groups represented by formulas (5L) and (5R) at the left and right ends; Equation (5L) represents the terminal base of the left-hand bond with the equation, and Equation (5R) represents the terminal base of the right-hand bond with the equation; A represents the following structure; R 0 Each of the above can independently represent an aryl group having 6 to 20 carbon atoms or a cycloalkyl group having 5 to 6 carbon atoms, wherein any hydrogen atom in the aryl group having 6 to 20 carbon atoms or the cycloalkyl group having 5 to 6 carbon atoms can be independently substituted by a fluorine atom or an alkyl group having 1 to 20 carbon atoms. R 1 Each of the following can independently represent a hydrogen atom, an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 5 to 6 carbon atoms, an arylalkyl group having 7 to 40 carbon atoms, or an alkyl group having 1 to 40 carbon atoms. In the aryl group having 6 to 20 carbon atoms, the cycloalkyl group having 5 to 6 carbon atoms, and the arylalkyl group having 7 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom or an alkyl group having 1 to 20 carbon atoms. In the alkylene group having 7 to 40 carbon atoms, any hydrogen atom can be substituted by a fluorine atom. Any -CH2- can be independently substituted by -O-, -CH=CH-, or a cycloalkylene group having 5 to 20 carbon atoms. In the alkyl group having 1 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom. Any -CH2- can be independently substituted by -O- or a cycloalkylene group having 5 to 20 carbon atoms. R 2 Each of the following can independently represent a hydroxyl group, an aryl group with 6 to 20 carbon atoms, a cycloalkyl group with 5 to 6 carbon atoms, an arylalkyl group with 7 to 40 carbon atoms, or an alkyl group with 1 to 40 carbon atoms. In the aryl group of the 6 to 20 carbon atoms, the cycloalkyl group with 5 to 6 carbon atoms, and the arylalkyl group with 7 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom or an alkyl group with 1 to 20 carbon atoms. In the alkylene group of the arylalkyl group with 7 to 40 carbon atoms, any hydrogen atom can be substituted by a fluorine atom. Any -CH2- can be independently substituted by -O-, -CH=CH-, or a cycloalkylene group with 5 to 20 carbon atoms. In the alkyl group with 1 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom. Any -CH2- can be independently substituted by -O- or a cycloalkylene group with 5 to 20 carbon atoms. R 3 Each of the above independently represents an alkylene group having 1 to 40 carbon atoms, wherein any -CH2- in the alkylene group having 1 to 40 carbon atoms may be independently substituted with -O- or a cycloalkylene group having 5 to 20 carbon atoms; R 4 Each of the following can independently represent an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 5 to 6 carbon atoms, an arylalkyl group having 7 to 40 carbon atoms, or an alkyl group having 1 to 40 carbon atoms. In the aryl group having 6 to 20 carbon atoms, the cycloalkyl group having 5 to 6 carbon atoms, and the arylalkyl group having 7 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom or an alkyl group having 1 to 20 carbon atoms. In the alkylene group having 7 to 40 carbon atoms, any hydrogen atom can be substituted by a fluorine atom. Any -CH2- can be independently substituted by -O-, -CH=CH-, or a cycloalkylene group having 5 to 20 carbon atoms. In the alkyl group having 1 to 40 carbon atoms, any hydrogen atom can be independently substituted by a fluorine atom. Any -CH2- can be independently substituted by -O- or a cycloalkylene group having 5 to 20 carbon atoms. R 5 Each can be independently represented as a hydroxyl group, hydrogen, or a crosslinking functional group of an alkenyl group having 2 to 40 carbon atoms, an alkyl group having 1 to 40 carbon atoms, a halogen, an acyl group having 1 to 15 carbon atoms, an alkoxy group having 1 to 15 carbon atoms, an oxime group having 1 to 15 carbon atoms, an amino group that may have a substituent, an amide group that may have a substituent, an aminooxy group that may have a substituent, or an ethylene alcohol residue having 2 to 15 carbon atoms, wherein the substituent in the amino and aminooxy groups has 1 to 15 carbon atoms; p represents a real number greater than 1, and z represents a positive real number; Indicates the location of the bond.
2. The siloxane polymer according to claim 1, further comprising repeating units represented by formula (2) and / or formula (3); R 2 R represents the expression in formula (4) of claim 1. 2 The same R 2 ; x and y represent positive real numbers independently.
3. The siloxane polymer according to claim 1, having repeating units represented by formula (2+4) and / or formula (4+2); R 2 R represents the expression in formula (4) of claim 1. 2 The same R 2 ; x and z represent positive real numbers independently.
4. The siloxane polymer according to claim 1 or 3, having at least one repeating unit selected from the formulas (4+2+3), (2+4+3), (2+3+4), (4+3+2), (3+4+2), and (3+2+4); R 2 R represents the expression in formula (4) of claim 1. 2 The same R 2 ; x, y, and z each represent a positive real number independently.
5. The siloxane polymer according to any one of claims 1 to 3, wherein R 2 Each can be independently methyl or phenyl, R 4 Each of the following can be independently phenyl, isobutyl, cyclopentyl, cyclohexyl, trifluoropropyl, nonafluorohexyl or pentafluorophenyl.
6. The siloxane polymer according to claim 4, wherein R 2 Each can be independently methyl or phenyl, R 4 Each of the following can be independently phenyl, isobutyl, cyclopentyl, cyclohexyl, trifluoropropyl, nonafluorohexyl or pentafluorophenyl.
7. The siloxane polymer according to any one of claims 1 to 3, wherein the weight average molecular weight is 2,000 to 10,000,000.
8. The siloxane polymer according to claim 4, wherein the weight average molecular weight is 2,000 to 10,000,000.
9. The siloxane polymer according to claim 5, wherein the weight average molecular weight is 2,000 to 10,000,000.
10. A siloxane polymer composition comprising the siloxane polymer as described in any one of claims 1 to 9 and a solvent.
11. A molded article formed by hardening a siloxane polymer as described in any one of claims 1 to 9 or a siloxane polymer composition as described in claim 10.
12. The molded article according to claim 11, wherein the haze value is less than 1%, the thermal decomposition temperature is in the range of 350°C to 450°C, and the coefficient of linear expansion is less than 200 ppm / K.
13. The molded article according to claim 11 has electrical insulation properties.
14. A shaped article, comprising: A hardened material formed by hardening the siloxane polymer as described in any one of claims 1 to 9 or the siloxane polymer composition as described in claim 10, and a substrate covered by said hardened material.
15. The molded article according to claim 14, wherein the difference in haze value between the molded article and the substrate is less than 1%, and the coefficient of linear expansion is less than 200 ppm / K.
16. The molded article according to claim 14 has electrical insulation properties.
Citation Information
Patent Citations
Bulk paper feeder
JP1990310232A
Method of producing silsesquioxane derivative having functional group and silsesquioxane derivative
JP2005015738A
Silicon compound
JP2006022207A
Crosslinkable siloxane polymer, siloxane-based crosslinkable composition and silicone membrane
JP2008280420A
Siloxane polymer, siloxane-based crosslinkable composition and silicone membrane
JP2010116462A